KURIKULUM PESANTREN MULTIKULTURAL (Melacak Muatan Nilai-Nilai Multikultural Dalam Kurikulum Pondok Pesantren Sunan Drajat Banjarwati Paciran Lamongan) - Sulton, Ahmad (ULUL ALBAB Jurnal Studi Islam, 2015)
The approach used in this study is a qualitative approach with case study design. Data collection was conducted by the researcher himself as a key instrument, whereas for determining the human data source using snowball sampling technique. Data was collected by means of; (1) in-depth interviews; (2) participant observation; and (3) study the documentation. For data analysis using descriptive techniques whose application is done in three flow of activities, namely data reduction, data presentation, and conclusion or verification. To determine the credibility of the data, conducted by a variety of techniques, namely (1) triangulation; (2) checking colleagues; and (3) checking members.